2011
DOI: 10.1159/000333420
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Overweight and Diabetes mellitus in Residential Psychiatric Patients

Abstract: Objective: To investigate the prevalence of and risk factors for overweight and diabetes mellitus in long-stay psychiatric inpatients. Method: Statistical analysis of data collected from medical, laboratory, and pharmacy files. Results: 80% of the 256 patients were suffering from schizophrenia or other psychotic disorders. The prevalence of diabetes mellitus was 15%. The prevalence of a disturbed glucose tolerance was 14%. Severe overweight (BMI > 30) was positively associated with the use of clozapine (odds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…(41) DM was defined as patients with twohour plasma glucose concentration ≥ 11.1 mmol/L or ≥ 200 mg/dL or who were known diabetic patients on medication in the 2010 National Health Survey in Singapore. (41) This finding was similar to previous studies on long-stay psychiatric inpatients in Singapore (26) and the Netherlands, (25) where the prevalence of DM was 16% and 15%, respectively. The general population had poorer blood control compared to inpatients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(41) DM was defined as patients with twohour plasma glucose concentration ≥ 11.1 mmol/L or ≥ 200 mg/dL or who were known diabetic patients on medication in the 2010 National Health Survey in Singapore. (41) This finding was similar to previous studies on long-stay psychiatric inpatients in Singapore (26) and the Netherlands, (25) where the prevalence of DM was 16% and 15%, respectively. The general population had poorer blood control compared to inpatients.…”
Section: Discussionsupporting
confidence: 88%
“…Patients with schizophrenia are often prescribed antidepressants and mood stabilisers, (17) which are associated, although to a lesser degree, with an increased risk for several physical diseases that include DM and dyslipidaemia, which is often linked to changes in body weight. (18,19) In terms of their physical health, patients with schizophrenia have higher body mass index, (20)(21)(22) and higher prevalence of DM, (23)(24)(25)(26) dyslipidaemia (27) and CVD (28) as compared to the general population. Furthermore, studies have also suggested that these patients have a lower probability of being screened and treated for such conditions, as reflected in a study by Nasrallah et al, (29) where they found low treatment rates for dyslipidaemia and DM among patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…4 Particularly, prevalence estimations of diabetes among patients with schizophrenia in the USA range from 14.2% in a retrospective cohort study, 5 18.7% in a cross-sectional study conducted in 819 patients with schizophrenia, 6 to 23.3% in another cross-sectional with 2231 patients, 7 with an alarming trend of increase over time (6.9% in 1997 to 14.5% in 2004). 8 In the European populations, prevalence is evaluated 15% in the Netherlands, 9 14.8% in a case-control study conducted in Sweden with 2.058.408 patients, 10 22% in a cross-sectional study in Finland, 11 whereas the prevalence of diabetes among patients with schizophrenia in the UK is estimated to be 11.3%. 12 Similarly in Asia, prevalence approaches 15.3% in a case-control study in India, 13 15% in Malaysia 14 and 8% in a case-control study in Singapore, however it included only 164 patients and 200 controls.…”
Section: Prevalence Of Type 2 Diabetes Among Patients With Schizophreniamentioning
confidence: 99%
“…The association of oral administration of clozapine and the concomitant derangement of glucose metabolism in the animal study by EI-Seweidy et al 51 helps us understand the insulin resistance and hyperglycemia induced by clozapine in schizophrenia patients who take the drugs orally. 5 , 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“… 1 3 However, the use of clozapine has been limited by its adverse effects on metabolism in schizophrenia patients, in addition to a risk of agranulocytosis. 4 The adverse metabolic effects associated with clozapine administration include weight gain, 5 , 6 glucose intolerance, 5 , 7 , 8 visceral obesity, 9 hypertension, 10 and dyslipidemia. 7 , 11 – 15 These metabolic syndromes may contribute to the increased cardiovascular mortality in schizophrenia patients.…”
Section: Introductionmentioning
confidence: 99%